THE MOVIE INDUSTRY AND REGIONAL ECONOMIC DEVELOPMENT: THE CASE OF ROCCO SCHIAVONE AND THE AOSTA VALLEY - Pagani, Valeria; Marques, Lenia (Brazilian Creative Industries Journal, 2022)
The movie industry is a creative sector that has the potential to contribute to (regional) economic development. Understanding the role of different stakeholders in the different parts of the process of movie production is paramount to provide an overview of the aspects that underlie an interaction that leads to regional economic development. Therefore, this study aims at investigating to what extent the interaction of stakeholders in the movie industry contributes to fostering regional economic development. A qualitative approach based on the single case study of Rocco Schiavone, an Italian tv series set in the Aosta Valley was used. A total of 14 in-depth interviews were recorded among different stakeholders using a snowball sampling. and the results point out to different interactions and power relations between stakeholders. During the three phases of pre-production, production and post-production, stakeholders also experience tensions. The paper concludes by underlining that despite the mainly positive outcome in terms of benefits for stakeholders and consequent economic development in the region, there are also challenges regarding the precariousness of jobs in the sector and the development of film-induced tourism products.